Medium-term priorities 2012-14 - (:unkn) unknown (Publications Office of the European Union, 2011)
"Cedefop's medium-term priorities define the multiannual framework which will guide its annual work programmes from 2012-2014. The priorities respond to the European policy framework for education and training which the European Commission and Member States redefined in 2009 and 2010, as the previous planning period was coming to an end." The following three medium-term priorities 2012-14 are described in Chapter 2: (1) supporting modernisation of VET systems; (2) careers and transitions - Continuing VET, adult and work-based learning; (3) analysing skills and competence needs to inform VET provision. "Chapter 3 sets the medium-term priorities in the context of Cedefop's mission as defined by its Founding Regulation. It defines the strategic objectives and explains how Cedefop will pursue these objectives and priorities. Cedefop's contributions must be well aligned with activities of other actors in the field to ensure relevance and value added of its work. This requirement is implemented through extensive networking with many partners as described in Chapter 4." (Hrsg., BIBB-Doku)
Keywords: CEDEFOP; Forschungsprogramm; Berufsbildungsforschung; Europäische Union; 2012-2014